2017
DOI: 10.1128/aem.00827-17
|View full text |Cite
|
Sign up to set email alerts
|

Stress Survival Islet 2, Predominantly Present in Listeria monocytogenes Strains of Sequence Type 121, Is Involved in the Alkaline and Oxidative Stress Responses

Abstract: The foodborne pathogen Listeria monocytogenes is able to survive a variety of stress conditions leading to the colonization of different niches like the food processing environment. This study focuses on the hypervariable genetic hot spot lmo0443 to lmo0449 haboring three inserts: the stress survival islet 1 (SSI-1), the single-gene insert LMOf2365_0481, and two homologous genes of the nonpathogenic species Listeria innocua: lin0464, coding for a putative transcriptional regulator, and lin0465, encoding an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
117
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(132 citation statements)
references
References 63 publications
13
117
1
1
Order By: Relevance
“…B), whereas SSI‐2 was only present in one isolate (CLIST 3864, L2‐SL121‐ST121‐CT4428). These stress survival islets contribute to Lm survival and grow in adverse environmental conditions, such as low pH and high salt concentrations (Ryan et al ., ) or alkaline and oxidative stress conditions (Harter et al ., ), facilitating the adaptation and persistence in production environments. A similar SSI prevalence was previously reported in Chile (Toledo et al ., ; P = 0.13; Chi‐square test), suggesting these mechanisms are typically present in L. monocytogenes , particularly in lineage II.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…B), whereas SSI‐2 was only present in one isolate (CLIST 3864, L2‐SL121‐ST121‐CT4428). These stress survival islets contribute to Lm survival and grow in adverse environmental conditions, such as low pH and high salt concentrations (Ryan et al ., ) or alkaline and oxidative stress conditions (Harter et al ., ), facilitating the adaptation and persistence in production environments. A similar SSI prevalence was previously reported in Chile (Toledo et al ., ; P = 0.13; Chi‐square test), suggesting these mechanisms are typically present in L. monocytogenes , particularly in lineage II.…”
Section: Resultsmentioning
confidence: 99%
“…[Color figure can be viewed at wileyonlinelibrary.com] ID27913 ID27916 ID27902 ID27929 ID27928 ID27925 ID27901 ID27910 ID27932 ID27924 ID27915 ID27905 ID27904 ID27908 ID27920 ID27909 ID27927 ID27933 ID27917 ID27934 ID27926 ID27907 ID27912 ID27898 ID27921 ID27923 ID27918 ID27906 ID27930 ID27899 ID27903 ID27922 ID27931 ID27914 ID27911 19 7 CLIST 1011 508 CLIST 3735 CT4437 CT4420 CT4436 CT4447 CT4418 CT4429 CT4432 CT4431 CT4423 CT4434 CT4433 CT4427 CT4015 CT4446 CT4445 CT4439 CT4425 CT4438 CT4443 CT4441 CT4421 CT4444 CT4426 CT720 CT4442 CT4429 CT4430 CT4440 CT4424 CT4422 CT4428 CT4449 CT4419 can be viewed at wileyonlinelibrary.com] stress conditions (Harter et al, 2017), facilitating the adaptation and persistence in production environments. A similar SSI prevalence was previously reported in Chile (Toledo et al, 2018; P = 0.13; Chi-square test), suggesting these mechanisms are typically present in L. monocytogenes, particularly in lineage II.…”
Section: Antibiotic and Stress Resistance Traitsmentioning
confidence: 99%
“…It possesses a 3.01 Mbp genome and a 62.2 kbp plasmid, designated pLM6179 (Schmitz-Esser et al, 2015b). Notably, the stress survival characteristics of L. monocytogenes 6179 have been extensively characterized (Müller et al, 2013(Müller et al, , 2014Casey et al, 2014;Makariti et al, 2015;Rychli et al, 2016;Harter et al, 2017;Naditz et al, 2019). L. monocytogenes strain R479a is an ST8 strain isolated from smoked salmon in Denmark in 1996 where it persisted for more than 2 years in the same FPE (Fonnesbech Vogel et al, 2001;Schmitz-Esser et al, 2015a).…”
Section: Bacterial Strains Used In This Studymentioning
confidence: 99%
“…Upon exposure to environmental stress conditions found in food and FPEs, L. monocytogenes responds by activating a wide variety of mechanisms that confer stress tolerance (Dutta et al, 2013;Müller et al, 2013;Harter et al, 2017;Bucur et al, 2018;Hingston et al, 2019). In addition to functional characterization, multiple gene expression analyses have implicated many genes in the response of L. monocytogenes to temperature, oxidative, disinfectant, pH, and osmotic stresses (Oliver et al, 2009;Soni et al, 2011;Tessema et al, 2012;Casey et al, 2014;Tang et al, 2015;Hingston et al, 2017b).…”
mentioning
confidence: 99%
“…Recent evidence has shown that L. monocytogenes ST121, a sequence type commonly associated with food and food environments, carries a stress survival islet (SSI-2) that confers increased survival under oxidative and alkaline stresses which are common in the food processing environment (Harter et al 2017). Overall, L. monocytogenes is well suited to surviving the various stresses presented by the fresh produce processing environment and may have a competitive advantage over other contaminating bacteria, facilitated through harbourage sites.…”
Section: Harbourage Sites and Persistent Strains In Food Processing Fmentioning
confidence: 99%